Lingual and aesthetic prominence of the Islamic Revolution poem - Ahmad Amiri khorasani; Mohammadsadegh Basiri; Zahra Anjomshoae (Literary Arts, 2019)
Abstract Today, fourteen years after the glorious Islamic Revolution and the growth of the Islamic Revolution poem, until now, this kind of poetry has not been studied scientifically and the studies have been more semantic and content-oriented; However, this research has tried to dwell on the structure of the language of the Islamic Revolution poetry and how to link the poetry templates on the subject of the Islamic Revolution. The method of this research is library and documentary, and then the data are presented descriptively-analytically. The result of the research shows that the axes such as freshness of language, compositional movement, novelty in rhymes and rows, the use of specific interpretations and images of the revolution and sacred defense, and the vocabulary of speech, constitute the prominence of the language of revolutionary poetry. By examining the various forms of the poem of the revolution, it is clear that the mantra of the Qesida has grown and prospered because of the epic spirit that ruled the country during the sixties. The revolutionary ghazard, with its features such as vertical order and the application of long weight, is especially important. The Masnavi Template is reborn with fresh and fresh rhymes. The Ghazal-Mathnawi format is expanding dramatically, and the revelation of a verbal weight in quatrains is a good platform for expressing the passionate feelings of the revolution and sacred defense. The main challenges in this paper are the dangers in the linguistic structure of the Islamic Revolution poetry and how to link the poetry forms with the subject of the Islamic Revolution. The importance of this issue in the present article is that the literature of the Islamic Revolution is often considered as meaningful literature, and its literal and structural features have not been taken into consideration; of course, it is not doubtful that the Islamic Revolution literature has a more semantic aspect, but with In the works, there are a number of structural and structural features and features. The verbal and structural prominence of the Islamic Revolution poem In terms of verbal and structural prominence, all forms of aesthetics are a literary work such as poetry that combines language and lexical modernizations, combining and using particular interpretations and images of the examples that we have addressed in these axes, respectively. 1-   Axes such as freshness of language, compositional movement, novelty in rhymes and rows, the use of specific interpretations and images of the sacred revolution and sacred defense, and the pace of vocabulary constitute the prominence of the revolutionary poetry. 2-   One of the points of the Islamic Revolution's poem is the tongue of the tongue, which sometimes has a freshness at the same time as the mold, language, freshness, and this freshness of language, thanks to the coincidence with the new poem and to be in the forefront of this way. 3-   The composition of the poetry revolution in terms of construction, it can be divided into three groups of additional composition, composition and phrases. 4-   Trying to use new rhymes and rows in different formats and using vocabulary and terms that reflect the vision of the revolution, and using the current and native rows of other linguistic features of revolution poetry. 5-   Use of specific interpretations and images of the war and the range of the lexical circle associated with the content of the particular thought of the revolution and the sacred defense, as well as the use of particular names, military terms and expressions, religious terms and expressions are the other factors for the novelty of the poetry language of the revolution. 6-   By examining the various forms of the poem of the revolution, it is clear that the form of the verse, although not very sparkling in contemporary poetry, is due to the epic spirit that ruled the revolution in the first years of the holy defense in the country, growth and prosperity Finds 7-   Ghazal in the poetry of revolution is of particular importance and is well received by the poets of the Islamic Revolution. Revolutionary ghosts have features such as vertical order, the use of high weight and novelty, and innovation. 8-   After the revolution, Masnavi's template was restored using new rhymes. The prevalence of Ghazal-Mathnavi's format is one of the structural features of the revolutionary poetry, which expanded dramatically during this period. 9-   The weight of the voice in the quatrains was a good basis for expressing the passionate feelings of the revolutionary period and the sacred defense of the sixties. 10-    The poets of the revolution in the middle years turned to new forms and introduced new insights into new poetry. The new poetry of the revolution is a narrative and supportive poetry and is usually long, but the new poetry is not a boring age. During the Islamic Revolution, Cari-kalamator grew dramatically, and the reason for its increase in the increase of the press and their release is the politicization of the country and the people after the revolution, and the breathing of the themes of satire and protest in the field of literature of the Islamic Revolution. This template found a significant difference in the present period before the revolution, and it was Cari-kalamator’s semantics in the era of the revolution.